β-lactam resistance mechanisms in Burkholderia pseudomallei and the tools used for their elucidation - Rholl, Drew Anders, author; Schwiezer, Herbert P., advisor; Dow, Steven W., committee member; Slayden, Richard A., committee member; Stargell, Laurie A., committee member (Colorado State University. Libraries, 2011)
A state of fear can arise from being unable to stop an impending threat. This can be the case of those infected with Burkholderia pseudomallei, the etiological agent of melioidosis. The 9-54% mortality rate, despite proper treatment, can be partially attributed to a combination of high levels of intrinsic and acquired antibiotic resistance causing treatment failure, unreliable/time-consuming diagnostics and a plethora of virulence factors. Even into the late 1980's, mortality was upwards of 80%. Its success as both a soil microbe and a highly antibiotic-resistant broad-host pathogen are in part due to its large genome and extensive metabolic capabilities. For these reasons and others, the Centers for Disease Control named B. pseudomallei a potential biothreat agent and a Category B select agent. The above mentioned attributes of B. pseudomallei make the bacterium's study both challenging and necessary. CDC select agent guidelines complicate the use of many effective molecular tools, making the job of elucidating the attributes of specific genetic elements difficult. Thus, the construction of new systems for genetic manipulation was required. Chapters 3 and 6 and parts of chapter 5 describe novel tools that have since been successfully used to genetically manipulate B. pseudomallei in an efficient and select-agent compliant fashion. Chapter 3 details construction of a transposon Himar1-based random mutagenesis system. Such systems have proven indispensable tools for the study of bacteria as they facilitate identification of metabolic pathways, virulence factors, antibiotic resistance mechanisms and other cellular processes. Chapter 6 describes improvements to existing tools, a new Escherichia coli mobilizer strain (RHO3) and an improved Tn7 transposase expression vector (pTNS3). RHO3 is the most versatile E. coli mobilizer strain engineered to date. It combines the plasmid mobilization efficiency of the widely used SM10 mobilizer strain with engineered kanamycin susceptibility and metabolic counterselection on rich media. The pTNS3 helper plasmid was engineered to express the Tn7 site-specific transposition pathway more efficiently by inclusion of the strong, broad-host-range P1 integron promoter in addition to the E. coli lactose-tryptophan Ptac hybrid promoter. Chapter 5 describes the application of a combination of the mini-Tn7-based single-copy chromosomal integration and expression system with the site-specific Cre recombinase system for temporary expression of a rescue gene aiding in characterization of essential genes. The work of defining novel resistance mechanisms is necessary to discover why recommended treatment regimens can fail. Use of ceftazidime in initial treatment of melioidosis halved the mortality rate. Because it is one of the few effective treatment options, resistance to this β-lactam is of great interest. Molecular definition of such mechanisms (chapters 4 and 5) could improve diagnostic capabilities, both clinically and in the case of a bioterrorism event. Chapter 4 describes the novel finding that the chromosomally encoded PenA β-lactamase is secreted via the twin arginine translocase system and that penA neighboring regulatory genes are most likely not involved in the regulation of expression of this gene. The work described in this chapter also established that PenA is the major B. pseudomallei β-lactam resistance mechanism and defined several mutations leading to ceftazidime and amoxicillin + clavulanic acid resistance. These findings form the basis for development of diagnostic tools for the detection of mutations causing high level resistance to clinically significant antibiotics which will allow initiation (biodefense) or redirection (clinical melioidosis) of proper antibiotic therapy. Work described in Chapter 5 defines deletion of the penicillin-binding protein 3 BPSS1219 as a novel ceftazidime resistance mechanism observed in B. pseudomallei strains isolated from patients that failed ceftazidime therapy. Through this body of work, I hope to have shed light on aspects of the biology of B. pseudomallei, novel genetic tools for its manipulation and novel mechanisms of β-lactam resistance.
Keywords: antibiotic resistance; melioidosis; genetic tools; Burkholderia pseudomallei